An Empowerment Of Educators And Parents In Increasing The Value Of Religious Moderation In Early Childhood: Increasing The Value Of Religious Moderation In Early Childhood - Syaikhon, Dr. Muhammad Syaikhon, SHI., MHI.; Djuwari, Djuwari; Berda Asmara , Berda Asmara; Fifi Khoirul Fitriyah , Fifi Khoirul Fitriyah; Nanang Rokhman Saleh , Nanang Rokhman Saleh; Andini Hardiningrum, Andini Hardiningrum (Community Development Journal, 2023)
Intolerance is one of the problems that occurs in Indonesia, especially in Gresik district. Educational institutions are the right solution to instill the value of moderation which can eliminate attitudes of intolerance, especially starting from early childhood education. Taman Asuh Anak Muslim (TAAM) Adinda is one of the early childhood education institutions located in Kepatihan village, Menganti sub-district, Gresik district. This institution consists of KB, RA, TPA, and TPQ. The problem faced at TAAM Adinda is that many educators and parents still do not understand the methods and importance of the value of religious moderation in early childhood. This community service activity was carried out to increase knowledge and understanding about increasing the value of religious moderation in early childhood at TAAM Adinda, Kepatihan Menganti Gresik. The time for implementing activities is 4 months. The method used was to gather educators and parents of TAAM Adinda students and then provide counseling about increasing the value of religious moderation in early childhood. This extension uses lecture and question and answer methods. The respondent's level of knowledge can be determined through a pre-test in the form of a questionnaire which will be filled in by the respondent to determine the level of knowledge regarding increasing the value of religious moderation in early childhood. The pre-test was carried out before the counseling was given, meanwhile to determine the increase in respondents' knowledge regarding increasing the value of religious moderation in early childhood, it could be determined by comparing the results of the post-test which was completed by the respondents after the counseling was carried out with the results of the pre-test. The output results of this community service activity are national journals and reports on increasing respondents' knowledge, understanding and awareness regarding increasing the value of religious moderation in early childhood. The conclusion in this community service activity is that the knowledge of educators and parents of students at the TAAM Adinda institution based on the pre-test results is mostly still low, while based on the post-test results, almost all participants have experienced an increase.